Different responses of soil bacterial species diversity and phylogenetic diversity to short-term nitrogen input in an alpine steppe at the source of Brahmaputra - Huang, Shaolin; Yu, Chengqun; Fu, Gang; Sun, Wei; Li, Shaowei; Xiao, Jianyu (Frontiers in Ecology and Evolution, 2022)
The Qinghai-Tibet Plateau has experienced an increase in N deposition/input due to global change. However, it remains unclear how the responses and whether the responses of soil bacterial diversity to short-term N input are consistent at different levels. Here, we investigated soil bacterial species and phylogenetic α-diversity and community composition based on a short-term nitrogen input experiment (five levels: 0, 2.5, 5, 10, and 20 g N m−2 y−1) in an alpine steppe at the source of Brahmaputra, using high-throughput sequencing technology. Short-term nitrogen input did not affect the species α-diversity and β-diversity of soil bacteria. However, soil bacterial phylogenetic α-diversity and dissimilarity increased with increasing nitrogen input. Different relative contributions and correlations of primary factors to species and phylogenetic diversity under short-term nitrogen input may result in different responses, in which ecological processes also play a role. Therefore, studying the response of soil bacteria to short-term nitrogen input should take into account not only the species level but also the phylogenetic level. We should pay close attention to the potential influence of short-term nitrogen deposition/fertilization on the soil bacterial community in the alpine steppe on the Tibetan Plateau.